Identification of key amino acid residues responsible for internal and external pH sensitivity of Orai1/STIM1 channels - Tsujikawa, Hiroto (Sci Rep, 2015)
Changes of intracellular and extracellular pH are involved in a variety of physiological and pathological processes, in which regulation of the Ca(2+) release activated Ca(2+) channel (I(CRAC)) by pH has been implicated. Ca(2+) entry mediated by I(CRAC) has been shown to be regulated by acidic or alkaline pH. Whereas several amino acid residues have been shown to contribute to extracellular pH (pH(o)) sensitivity, the molecular mechanism for intracellular pH (pH(i)) sensitivity of Orai1/STIM1 is not fully understood. By investigating a series of mutations, we find that the previously identified residue E106 is responsible for pH(o) sensitivity when Ca(2+) is the charge carrier. Unexpectedly, we identify that the residue E190 is responsible for pH(o) sensitivity when Na(+) is the charge carrier. Furthermore, the intracellular mutant H155F markedly diminishes the response to acidic and alkaline pH(i), suggesting that H155 is responsible for pH(i) sensitivity of Orai1/STIM1. Our results indicate that, whereas H155 is the intracellular pH sensor of Orai1/STIM1, the molecular mechanism of external pH sensitivity varies depending on the permeant cations. As changes of pH are involved in various physiological/pathological functions, Orai/STIM channels may be an important mediator for various physiological and pathological processes associated with acidosis and alkalinization.